EDUKASI JAJANAN SEHAT DENGAN METODE CERAMAH MENGGUNAKAN PERMAINAN KARTU KUARTET PADA ANAK USIA SEKOLAH DASAR - Sazida, Hanna; Tahlil, Teuku; Ridwan, Arfiza (LPPM Universitas Flores, 2025)
The health of primary school-age children is an important component of public health development. In this phase, children are in a critical period of growth and development, as well as at risk of health problems, one of which is due to unhealthy snack consumption behaviour. This community nursing intervention aims to increase knowledge and awareness of healthy snacks among children in one of the elementary schools in Aceh Besar District, Aceh Province. The educational method used lectures and quartet card games adapted to the age of the children. Academic activities were divided into four parts: pre-test, material delivery, quartet card game, and post-test. The evaluation results showed that after the intervention, the proportion of students with high knowledge (80%) was higher than those with medium (20%) and low expertise (0%). Using lecture methods and quartet card games can increase the knowledge and awareness of elementary school students about healthy snacks. Schools, community nurses and other related professionals can consider applying lecture methods and quartet card games to improve students' snacking behaviour at school.